The water supply service during the COVID-19 pandemic among people of concern in Nigeria - Dyah Suryani; Novin Yetiani; Adi Yeremia Mamahit; Hairil Akbar; Ade Rahmawati; Rizki Amartani; Sunarti Sunarti; Abu Bakar Yakubbu Abbani; Maretalinia Maretalinia (International Journal of Public Health Science (IJPHS), 2023)
Refugees in the destination countries might have some risks including lack of water supply. Nigeria as one of the destination countries for people of concern (PoCs) including refugees also faced the lack of access to water supply, especially during the COVID-19 pandemic. This study aimed to examine the factors related to reduced access to water supply in refugee camps in Nigeria during COVID-19 pandemic. This study used the secondary data available from UNHCR in Nigeria 2020. The survey used disproportionate stratified random sampling. After data cleaning, the data from 4,016 households were examined in this study. The interview has been done using the computer-assisted telephone interview. The factors related to the reduced access to water supply were living in Adamawa, Benue, Ogun, Taraba, Yobe, and Borne states, coming from Cameroon, Democratic Republic of Congo, Mali, and Syria, having household member 6-15 persons, having household income 41,000- 60,000 Naira per month, and had low awareness about COVID-19. The demographic and economic factors were the most significantly related to reduced access to the water supply.